Type studies of J. Rick’s corticioid homobasidiomycetes (agaricomycetes, basidiomycota) housed in the herbarium Anchieta (PACA) - Baltazar, Juliano M. (2016)
A revision of J. Rick’s type collection at Herbarium Anchieta (PACA) was carried out and 134 specimens corresponding to 115 taxa of corticioid homobasidiomycetes (Basidiomycota) proposed by Rick were studied. Sixteen taxa are accepted: Epithele bambusina is accepted in this genus, Poria bambusarum is accepted as Fomitiporia bambusarum (syn. Phellinus bambusarum), and the following new combinations are proposed: Clavulicium flavidulum, Dendrothele triangulispora, Fibrodontia fimbriata (syn. Fibrodontia gossypina), Hyphoderma cinereoalbum (syn. Hyphoderma variolosum), Hyphoderma molliusculum, Hyphodontia corticioidea (syn. Hyphodontia sphaerospora), Hypochnicium horridulum (syn. Hypochnicium gomezii), Parvodontia albocrustacea, Peniophora carneorosea (syn. Peniophora laxitexta), Peniophora conspersa, Peniophora gomezii (syn. Peniophora confusa), Phlebia subconspersa (syn. Mycoacia subconspersa), Resinicium luteosulphureum (syn. Resinicium friabile), and Vararia calospora (syn. Vararia tropica). Forty-four taxa are considered synonyms of older names, ten names are invalid and three are illegitimate. Furthermore, eight lectotypes and one epitype are designated. Forty-three taxa remain unsolved mainly due to the poor condition of Rick’s specimens. Twelve unpublished names were found among Rick’s type collections, and their determination is given whenever possible. Descriptions and drawings are provided to taxa poorly known from literature.